Smart Parking System Based on RFID & GSM Technology - Chandru S; Deva Prasath K; Abishek G; Guru Prasath KS; Dr. Niresh J (International Journal of Engineering and Management Research, 2023)
In the modern world with about a billion vehicles present around the globe, and being in a densely populated country like India creates the need for an efficient parking system and with world advancing towards automation, there is also a need for an automated parking system. Mainly the problem of parking arises in big cities and this causes problems like traffic congestion, driver frustration & air pollution, etc. The issue mainly arises from not knowing whether the parking spaces is available at any given point of time. Even if known, many vehicles may be competing for limited parking spaces causing severe traffic congestions. Even there are problems that can be caused with regards to the parking management. It may be difficult for the parking management to organise the parking of the vehicles in an orderly manner. Thus we are trying to resolve the problems stated by developing an RFID based smart parking system that monitors the availability of idle parking slots and guides the vehicle to the nearest such slot by sending a message to the mobile number registered in the vehicle’s RFID. The proposed system uses infrared transmitter-receiver pairs that remotely communicate the status of parking occupancy to the Arduino UNO microcontroller and displays the vacant slots on the display at the entrance of the parking so that the user gets to know the availability /unavailability of parking space prior to his/her entry into the parking place. Implementation involves minimal human interaction and provides a seamless parking experience thereby reducing a lot of time wasted by the user in parking his/her vehicle. Key Words: Parking System, RFID, Arduino UNO